1995
DOI: 10.1017/s0889189300006081
|View full text |Cite
|
Sign up to set email alerts
|

The relative sustainability of alternative, conventional, and reduced-till farming systems

Abstract: We compared the agronomic, economic, and ecological performance of alternative (organic), conventional, and reduced-till farming systems over a 7-year period. We evaluated the sustainability of the various systems regarding several concerns, including soil erosion, pollution potential, whole-farm productivity, energy use, environmental stress, economic performance, and farm size. The alternative systems relied primarily on forage legumes (alfalfa or clover) as substitutes for the pesticides and commercial fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(41 citation statements)
references
References 7 publications
2
39
0
Order By: Relevance
“…However, there are indications that the economic performance of alternative farming systems can be comparable to, if not better than, that of conventional farming systems. This is supported by work at national levels as well as within-farm levels Kremen 2002, 2003;Madden 1987;Offermann and Nieberg 1999;Pacini et al 2003;Padel and Lampkin 1994;Smolik et al 1995). The findings of Smolik et al (1995) support the conclusions of Rosset (1999) by suggesting that the widespread adoption of organic farming in their study system would tend to counter the trend of increasing farm size: conventional farming was calculated to require a greater area for the same level of profitability as a smaller organic farm in most cases.…”
Section: Alternative Productionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, there are indications that the economic performance of alternative farming systems can be comparable to, if not better than, that of conventional farming systems. This is supported by work at national levels as well as within-farm levels Kremen 2002, 2003;Madden 1987;Offermann and Nieberg 1999;Pacini et al 2003;Padel and Lampkin 1994;Smolik et al 1995). The findings of Smolik et al (1995) support the conclusions of Rosset (1999) by suggesting that the widespread adoption of organic farming in their study system would tend to counter the trend of increasing farm size: conventional farming was calculated to require a greater area for the same level of profitability as a smaller organic farm in most cases.…”
Section: Alternative Productionmentioning
confidence: 75%
“…This is supported by work at national levels as well as within-farm levels Kremen 2002, 2003;Madden 1987;Offermann and Nieberg 1999;Pacini et al 2003;Padel and Lampkin 1994;Smolik et al 1995). The findings of Smolik et al (1995) support the conclusions of Rosset (1999) by suggesting that the widespread adoption of organic farming in their study system would tend to counter the trend of increasing farm size: conventional farming was calculated to require a greater area for the same level of profitability as a smaller organic farm in most cases. Additionally, supporting the viability of alternative agriculture in terms of the level of difficulty in its management is the work of Pacini et al (2003), Lockeretz (1995), and the comprehensive survey of sustainable farms by Pretty and Hine (2001).…”
Section: Alternative Productionmentioning
confidence: 75%
“…According to (Smolik, Dobbs, & Rickerl, 1995), OF is more profitable than conventional farming in the long-term. Studies conducted by (Badgley et al, 2007) have shown that OF can produce almost the same yield of conventional farming in developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Low or no till systems decrease direct energy inputs but can increase indirect energy by requiring more herbicides, pesticides, and other chemicals (Smolik et al, 1995). Seen in a more global perspective (that is beyond a given farm), no tillage systems are often crop monocultures which entail off-farm degradation through intensive livestock systems that make use of energy intensive feed, let alone direct pollution externalities.…”
Section: Mechanisationmentioning
confidence: 99%